Analisis Efektivitas Tata Kelola Administrasi Realisasi APBN di Kanwil DJPb Riau Tahun 2026 - Sinaga, Pandu Hidayat; Ramadhan, Rian Rahmat; Zaki, Hammam; Rahayu, Norra Isnasia; Rudi, Asep (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2026)
This study aims to analyze the effectiveness of administrative governance in APBN realization at the Regional Office of the Directorate General of Treasury (Kanwil DJPb) of Riau Province. The study employed a descriptive qualitative approach using in-depth interviews and document reviews as data collection techniques. The findings indicate that the administrative governance of APBN realization at the Riau Regional Office of DJPb has been implemented quite effectively, although it has not fully achieved the established performance targets. The main obstacles include coordination issues among work units, technical disruptions in the financial information system, and regulatory changes. The effectiveness of administrative governance is influenced by the quality of the reporting system, the competence of personnel, and adequate information technology support. This study recommends enhancing human resource capacity, strengthening digital infrastructure, and optimizing coordination among work units in Riau Province.